True hermaphroditism in a wistar rat - Madheswaran , R.; Pande , V. V.; Kalaiselvan, P.; Mathur , K. Y.; Shelar, P. D.; Bhelonde, J. J.; Udupa, Venkatesha; Shingatgeri, V. M. (Brazilian Journal of Veterinary Pathology, 2009)
A rare case of true hermaphroditism was observed in a 9-week-old presumed female Wistar rat. This rat did not reveal any untoward clinical signs, food consumption, body weight gain and changes in haemato-biochemical parameters. Grossly, rat showed reduced size of the left ovary and shortened uterine horn. Microscopically, ovotestis was observed in the left ovarian tissue. Ovary consisted of numerous developing follicles at different stages of development with absence of corpora lutea. Developing testis contained seminiferous tubules lined with sertoli cells and sparse spermatogonial population. Left oviduct resembling developing epididymis consisting of tubules embedded in proliferating fibrous connective tissue, lined with multilayered ciliated columnar epithelial cells. Most of them were empty but, few had eosinophilic secretion and some of them contained exfoliated germ cells. Left uterine horn showed increased stromal connective tissue without proliferation of endometrial glands. A histopathological examination of left ovarian tissue implies a case of true hermaphroditism.